Penerapan Karakteristik PMRI untuk Meningkatkan Hasil Belajar Pecahan Senilai Kelas IV Sekolah Dasar - Wati, Dian Fitria; Ahmad, Syafri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
This research is motivated by student learning outcomes that are not in accordance with what is expected. The teacher has not linked learning with the child's real life or realistic problems and has not provided an opportunity for students to discover mathematical concepts that they know. The purpose of this study is to describe the application of characteristics realistic mathematics education Indonesia approach to improving learning outcomes fraction worth materials class IV SDN 19 ATTS Bukittinggi.             This type of research is classroom action research using qualitative and quantitative approaches. The study was conducted in two cycles consisting of planning, implementation, observation, and reflection. Research data in the form of observations and actions as well as test results. The data source is the process and results of the implementation of student learning on fraction worth material using the characteristics Realistic Mathematics Education Indonesia (PMRI) approach. The research subjects were 24 teacher and grade IV students consisting of 10 mens and 14 womens.             The results showed that the first, an increase in planning the implementation of learning using the PMRI approach that is in the first cycle obtained a percentage of 83.92% increased in the second cycle to 92.85% with very good qualifications. It can be concluded that there was an increase of 8.93%. Improvements also occurred in the implementation of learning using the PMR approach from both the teacher and student aspects. In the aspect of teachers in the first cycle to get a percentage of 80% increased in the second cycle to 90%. It can be concluded that an increase of 10%. And also in the aspect of students in the first cycle to get a percentage of 80% increased in the second cycle to 90%. It can be concluded that an increase of 10%. Improvements were also seen in student learning outcomes using the PMR approach ie in the first cycle the average class obtained by students was 75,73% increased in the second cycle to 87,29% an increase of 11,56%. It can be concluded that the characteristics PMRI approach can improve student learning outcomes in fraction worth in Class IV SDN 19 ATTS Bukittinggi.